Über die räuberische Tätigkeit von Formica rufa L. und Formica nigricans Emery außerhalb einer Insekten-Massenvermehrung (Hymenoptera: Formicidae). - Schwenke, Wolfgang (Contributions to Entomology = Beiträge zur Entomologie, 1957)
Two colonies of Formica rufa L. (within pine woods aged forty) and one colony of Formica nigricans Emery (on a little fallow land surrounded by a pine wood aged thirty, a pine culture and a beechtree culture) were investigated in 1953, 1955 and 1956 relative to a) number of workers per minute running to the nest, b) portion of workers carrying material, c) quality of carried material and proportion vegetal/animal material, d) size and form of the area of activity, e) ant-density per square meter at a fixed distance from the nest, f) number and position of the trees visited by ants and of the ant-streets and g) reduction of the density of Coleophora laricella Hb. - caterpillars on larch-trees by Formica nigricans. The results are discussed with regard to biocoenological and economical aspects.